When economy meets ecology, is it truly conflicted? A dashboard approach to assess the sustainability performance of European tropical tuna purse seine fisheries - Sandra Ougier; Pascal Bach; François Le Loc'h; Joël Aubin; Didier Gascuel (Science of The Total Environment, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

The rostral micro‐tooth morphology of blue marlin, Makaira nigricans - Korbinian Pacher; Michael Breuker; Matthew J. Hansen; Ralf H. J. M. Kurvers; Jan Häge; Felicie Dhellemmes; Paolo Domenici; John F. Steffensen; Stefan Krause; Thomas Hildebrandt; Guido Fritsch; Pascal Bach; et al. (Journal of Fish Biology, 2024)
Billfish rostra potentially have several functions; however, their role in feeding is unequivocal in some species. Recent work linked morphological variation in rostral micro‐teeth to differences in feeding behavior in two billfish species, the striped marlin ( Kajikia audax ) and the sailfish ( Istiophorus platypterus ). Here, we present the rostral micro‐tooth morphology for a third billfish species, the blue marlin ( Makaira nigricans ), for which the use of the rostrum in feeding behavior is still undocumented from systematic observations in the wild. We measured the micro‐teeth on rostrum tips of blue marlin, striped marlin, and sailfish using a micro–computed tomography approach and compared the tooth morphology among the three species. This was done after an analysis of video‐recorded hunting behavior of striped marlin and sailfish revealed that both species strike prey predominantly with the first third of the rostrum, which provided the justification to focus our analysis on the rostrum tips. In blue marlin, intact micro‐teeth were longer compared to striped marlin but not to sailfish. Blue marlin had a higher fraction of broken teeth than both striped marlin and sailfish, and broken teeth were distributed more evenly on the rostrum. Micro‐tooth regrowth was equally low in both marlin species but higher in sailfish. Based on the differences and similarities in the micro‐tooth morphology between the billfish species, we discuss potential feeding‐related rostrum use in blue marlin. We put forward the hypothesis that blue marlin might use their rostra in high‐speed dashes as observed in striped marlin, rather than in the high‐precision rostral strikes described for sailfish, possibly focusing on larger prey organisms.

An application of Electronic Monitoring System to optimize onboard observation protocols for estimating tropical tuna purse seine discards - Karine Briand; Philippe S. Sabarros; Alexandra Maufroy; Anne-Lise Vernet; Arthur Yon; Antoine Bonnieux; Michel Goujon; Pascal Bach (Regional Studies in Marine Science, 2023)

Lacunae rostralis: A new structure on the rostrum of sailfish Istiophorus platypterus - Jan Häge; Matthew J. Hansen; Korbinian Pacher; Félicie Dhellemmes; Paolo Domenici; John F. Steffensen; Michael Breuker; Stefan Krause; Thomas B. Hildebrandt; Guido Fritsch; Pascal Bach; Philippe S. Sabarros; et al. (Journal of Fish Biology, 2022)
Recent comparative studies of billfishes (Istiophoridae and Xiphiidae) have provided evidence of differences in the form and function of the rostra (bill) among species. Here, we report the discovery of a new structure, lacuna rostralis, on the rostra of sailfish Istiophorus platypterus , which is absent on the rostra of swordfish Xiphias gladius , striped marlin Kajikia audax and blue marlin Makaira nigricans . The lacunae rostralis are small cavities that contain teeth. They were found on the ventral rostrum surface of all I. platypterus specimens examined and dorsally in half of them. Ventrally, the lacunae rostralis were most prominent in the mid‐section of the rostrum. Dorsally, they occurred closer to the tip. The density of lacunae rostralis increased towards the rostrum tip but, because they are smaller in size, the percentage of rostrum coverage decreased. The teeth located within the lacunae rostralis were found to be different in size, location and orientation from the previously identified micro‐teeth of billfish. We propose two potential functions of the lacunae rostralis that both relate to the use of the bill in feeding: mechanoreception of prey before tapping it with the bill and more efficient prey handling via the creation of suction, or physical grip.

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Effect of pelagic longline bait type on species selectivity: a global synthesis of evidence - Eric Gilman; Milani Chaloupka; Pascal Bach; Hannah Fennell; Martin Hall; Michael Musyl; Susanna Piovano; Francois Poisson; Liming Song (Reviews in Fish Biology and Fisheries, 2020)
Fisheries can profoundly affect bycatch species with ‘slow’ life history traits. Managing bait type offers one tool to control species selectivity. Different species and sizes of marine predators have different prey, and hence bait, preferences. This preference is a function of a bait’s chemical, visual, acoustic and textural characteristics and size, and for seabirds the effect on hook sink rate is also important. We conducted a global meta-analysis of existing estimates of the relative risk of capture on different pelagic longline baits. We applied a Bayesian random effects meta-analytic regression modelling approach to estimate overall expected bait-specific catch rates. For blue shark and marine turtles, there were 34% (95% HDI: 4–59%) and 60% (95% HDI: 44–76%) significantly lower relative risks of capture on forage fish bait than squid bait, respectively. Overall estimates of bait-specific relative risk were not significantly different for seven other assessed taxa. The lack of a significant overall estimate of relative capture risk for pelagic shark species combined but significant effect for blue sharks suggests there is species-specific variability in bait-specific catch risk within this group. A qualitative literature review suggests that tunas and istiophorid billfishes may have higher catch rates on squid than fish bait, which conflicts with reducing marine turtle and blue shark catch rates. The findings from this synthesis of quantitative and qualitative evidence support identifying economically viable bycatch management measures with acceptable tradeoffs when multispecies conflicts are unavoidable, and highlight research priorities for global pelagic longline fisheries.

The effects of mesoscale oceanographic structures and ambient conditions on the catch of albacore tuna in the South Pacific longline fishery - Cheng Zhou; Pingguo He; Liuxiong Xu; Pascal Bach; Xuefang Wang; Rong Wan; Hao Tang; Yu Zhang (Fisheries Oceanography, 2020)
Albacore tuna ( Thunnus alalunga ) exhibit patchy concentrations associated with biological process at a wide range of spatial scales, resulting in variations in their catchability by fishing gears. Here, we investigated the association of catch variation for pelagic longlines in the South Pacific Ocean with oceanographic mesoscale structures (in horizontal dimension) and ambient conditions (in vertical dimension). The distribution of albacore tuna as indicated by catch per unit effort (CPUE) of longlines was significantly related to the presence of mesoscale structures, with higher CPUE found at locations closer to thermal fronts and with greater gradient magnitudes, as well as areas marked by peripheral contour line of the anticyclone indicated by Sea Surface Height Anomalies ~0.05 m. Surface mesoscale current velocity had the negative effect on the catch, probably as a result of decreased catchability by shoaling the hook depth. Vertical distribution of albacore in the survey region of South Pacific Ocean was hardly restricted by ambient temperature and oxygen concentration, though effect of ambient temperature was relevant and showed a negatively linear correlation with CPUE at the range of 20–24°C. On the contrary, albacore distribution was evidently dominated by the water depth and showed strong preference on water depth of 200 m, which was likely a representative feeding layer. The presence of prey resources and their accessibility by albacore revealed by mesoscale structures in the biological and physical processes, and catchability determined by the location of the baited hooks comprehensively contribute to the variability of catch.

Distribution patterns and population structure of the blue shark ( Prionace glauca ) in the Atlantic and Indian Oceans - Rui Coelho; Jaime Mejuto; Andrés Domingo; Kotaro Yokawa; Kwang‐Ming Liu; Enric Cortés; Evgeny V. Romanov; Charlene da Silva; Fábio Hazin; Freddy Arocha; Aldrin Masawbi Mwilima; Pascal Bach; et al. (Fish and Fisheries, 2018)
The blue shark ( Prionace glauca ) is the most frequently captured shark in pelagic oceanic fisheries, especially pelagic longlines targeting swordfish and/or tunas. As part of cooperative scientific efforts for fisheries and biological data collection, information from fishery observers, scientific projects and surveys, and from recreational fisheries from several nations in the Atlantic and Indian Oceans was compiled. Data sets included information on location, size and sex, in a total of 478,220 blue shark records collected between 1966 and 2014. Sizes ranged from 36 to 394 cm fork length. Considerable variability was observed in the size distribution by region and season in both oceans. Larger blue sharks tend to occur in equatorial and tropical regions, and smaller specimens in higher latitudes in temperate waters. Differences in sex ratios were also detected spatially and seasonally. Nursery areas in the Atlantic seem to occur in the temperate south‐east off South Africa and Namibia, in the south‐west off southern Brazil and Uruguay, and in the north‐east off the Iberian Peninsula and the Azores. Parturition may occur in the tropical north‐east off West Africa. In the Indian Ocean, nursery areas also seem to occur in temperate waters, especially in the south‐west Indian Ocean off South Africa, and in the south‐east off south‐western Australia. The distributional patterns presented in this study provide a better understanding of how blue sharks segregate by size and sex, spatially and temporally, and improve the scientific advice to help adopt more informed and efficient management and conservation measures for this cosmopolitan species.

Normal phase HPLC-based activity profiling of non-polar crude plant extracts – acetylcholinesterase inhibiting guttiferones from Montrouziera cauliflora as a case study - Anne Landreau; Samuel Bertrand; Claudia Simoes-Pires; Laurence Marcourt; Dang Bach Taï; Marc Litaudon; David Guilet; Pascal Richomme; Pierre-Alain Carrupt; Jean-Luc Wolfender (Natural Product Research, 2016)

Exploratory and Instantaneous Swimming Speeds of Amphidromous Fish School in Shallow-Water Coastal Lagoon Channels - Patrice Brehmer; Jean Guillard; Pablo I. Caballero Pinzon; Pascal Bach (Estuaries and Coasts, 2011)

Simultaneous observations of tuna movements and their prey by sonic tracking and acoustic surveys - Erwan Josse; Pascal Bach; Laurent Dagorn (Hydrobiologia, 1998)